2024
DOI: 10.3390/w16050627
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Soil-Water Characteristic Curves (SWCC) of Expansive Soil: Effects of Sand Content, Initial Saturation, and Initial Dry Unit Weight

Ammar Alnmr,
Mounzer Omran Alzawi,
Richard Ray
et al.

Abstract: Soil-water characteristic curve (SWCC) is an essential parameter in unsaturated soil mechanics, and it plays a significant role in geotechnical engineering to enhance theoretical analysis and numerical calculations. This study investigated the effects of key factors, such as the percentage of sand, initial degree of saturation, and initial dry unit weight, on the SWCC of expansive soil by measuring the matric suction using a pressure apparatus method. The empirical equation of SWCC was obtained using the Van G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Balancing the sand fraction is critical in engineering applications because it improves soil performance and reduces the negative impacts of cracking in expansive soil [19]. The addition of sand to expansive soils has been extensively investigated by many researchers to determine its effect on the soil parameters [10,[20][21][22][23][24][25][26]. Previous studies have confirmed that increasing the percentage of sand increases the unconfined compressive strength (UCS) of expansive soils.…”
Section: Sand As An Additive Materials and Its Impact On Soil Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Balancing the sand fraction is critical in engineering applications because it improves soil performance and reduces the negative impacts of cracking in expansive soil [19]. The addition of sand to expansive soils has been extensively investigated by many researchers to determine its effect on the soil parameters [10,[20][21][22][23][24][25][26]. Previous studies have confirmed that increasing the percentage of sand increases the unconfined compressive strength (UCS) of expansive soils.…”
Section: Sand As An Additive Materials and Its Impact On Soil Parametersmentioning
confidence: 99%
“…The Soil-Water Characteristic Curve (SWCC) is a fundamental relationship between the content of water and soil suction [29] that effectively describes the behavior of unsaturated soils. The retention behavior of soil water can be influenced by various factors, including dry unit weight, degree of saturation, stress conditions, and soil amendments [26,30,31]. The degree of saturation, moisture content, and volumetric water content are terms commonly used to describe the amount of water in the soil.…”
Section: Sand As An Additive Materials and Its Impact On Soil Parametersmentioning
confidence: 99%